If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 360 = (5x + 5) * 2x Reorder the terms: 360 = (5 + 5x) * 2x Reorder the terms for easier multiplication: 360 = 2x(5 + 5x) 360 = (5 * 2x + 5x * 2x) 360 = (10x + 10x2) Solving 360 = 10x + 10x2 Solving for variable 'x'. Reorder the terms: 360 + -10x + -10x2 = 10x + -10x + 10x2 + -10x2 Combine like terms: 10x + -10x = 0 360 + -10x + -10x2 = 0 + 10x2 + -10x2 360 + -10x + -10x2 = 10x2 + -10x2 Combine like terms: 10x2 + -10x2 = 0 360 + -10x + -10x2 = 0 Factor out the Greatest Common Factor (GCF), '10'. 10(36 + -1x + -1x2) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(36 + -1x + -1x2)' equal to zero and attempt to solve: Simplifying 36 + -1x + -1x2 = 0 Solving 36 + -1x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -36 + x + x2 = 0 Move the constant term to the right: Add '36' to each side of the equation. -36 + x + 36 + x2 = 0 + 36 Reorder the terms: -36 + 36 + x + x2 = 0 + 36 Combine like terms: -36 + 36 = 0 0 + x + x2 = 0 + 36 x + x2 = 0 + 36 Combine like terms: 0 + 36 = 36 x + x2 = 36 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. + 0.25 + x2 = 36 + 0.25 Combine like terms: + 0.25 = 1.25 1.25 + x2 = 36 + 0.25 Combine like terms: 36 + 0.25 = 36.25 1.25 + x2 = 36.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 36.25 Calculate the square root of the right side: 6.020797289 Break this problem into two subproblems by setting (x + 0.5) equal to 6.020797289 and -6.020797289.Subproblem 1
x + 0.5 = 6.020797289 Simplifying x + 0.5 = 6.020797289 Reorder the terms: 0.5 + x = 6.020797289 Solving 0.5 + x = 6.020797289 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 6.020797289 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 6.020797289 + -0.5 x = 6.020797289 + -0.5 Combine like terms: 6.020797289 + -0.5 = 5.520797289 x = 5.520797289 Simplifying x = 5.520797289Subproblem 2
x + 0.5 = -6.020797289 Simplifying x + 0.5 = -6.020797289 Reorder the terms: 0.5 + x = -6.020797289 Solving 0.5 + x = -6.020797289 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -6.020797289 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -6.020797289 + -0.5 x = -6.020797289 + -0.5 Combine like terms: -6.020797289 + -0.5 = -6.520797289 x = -6.520797289 Simplifying x = -6.520797289Solution
The solution to the problem is based on the solutions from the subproblems. x = {5.520797289, -6.520797289}Solution
x = {5.520797289, -6.520797289}
| -110=-5(7-3x) | | 5(t-4)=36 | | 4x^2+5x-6(x^2+x-2)= | | 5=20+r | | 10-x-1(-2)-8+4x= | | 16.7x=79.49 | | 3/5x-4=12 | | 4y=-9x | | 65/2 | | (y-7)(y-7)(y-7)=6 | | v+10=-1 | | 8316=(14784)r(9) | | 4x-6(2x-3)= | | -7+4m=-5+6m | | 8w-3/2=13-7w-1/8 | | 2/3y-1=7/9 | | 34-4-4b=18 | | 3-(x-4)=2x-6+5x | | 100/6x=79.49 | | 8+(-8)=16 | | 9(x-6)(x+1)=0 | | 5x+2(1-x)=2(2x-4) | | 6y-(y-2)=12/0.064/3 | | 9+v=-5 | | 4p^2-(2p^2-3p+1)= | | 11x-4=10x+5-6 | | x-5/8/2x-10/56 | | 3(x+4)-2(3x-5)+4x-1=4(2x-1)-(2x+5) | | 2x^2=7200 | | 79.49=100/6x | | -7x-27=8-1(1x-19) | | X/9=14/18 |